1990
DOI: 10.3109/08977199009108277
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Growth Factors Present in Bone Matrix with Bone Cells: Effects on DNA Synthesis and Alkaline Phosphatase

Abstract: It has been shown that bone cells produce and secrete several growth factors (GFs) which are also found in the bone matrix. To investigate the role of these growth factors in bone cell metabolism, we compared the effects of different factors separately and in combination with respect to osteoblastic cell proliferation and differentiation. While basic fibroblast GF (FGF), transforming GF beta-1 (TGF beta), and platelet-derived GF (PDGF) enhance DNA synthesis, they had the opposite effect on alkaline phosphatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 32 publications
5
48
0
Order By: Relevance
“…The effects of these growth factors on cell behavior and bone-healing sequences have been thoroughly studied [4,5,7,11,15,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of these growth factors on cell behavior and bone-healing sequences have been thoroughly studied [4,5,7,11,15,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Collagen and protein synthesis by osteoblasts is also stimulated by PDGF, but also requires the presence of IGF-I [7]. PDGF probably enhances the secretion of IGF-I by the osteoblasts and mesenchymal stem cells, which then accelerates the formation of a collagenous matrix [11]. PDGF also seems to enhance the activity of BMP in promoting cartilage and bone formation [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported the efficacy of bone morphogenetic protein (BMP) in facilitating spinal fusion [5]. The beneficial effects of platelet-derived growth factor (PDGF) on bone formation in vitro has also been described previously [9,10,18,20,22,34,36,37], while in vivo stimulation of bone formation by transforming growth factor-β (TGF-β) has been shown in animal models [20,30,33]. Both PDGF and TGF-β have mitogenic effects on fibroblasts, osteoblasts, and mesenchymal cells by the stimulation of DNA synthesis and cell replication [12].…”
Section: Introductionmentioning
confidence: 99%
“…One study [33]demonstrated that the effect of TGF-β is a local one, with no effects on bone formation at distant sites. Other authors have noted that multiple growth factors are present at the same time at the site of bone formation and have a synergistic effect on one another [22]. This led to the concept of providing high concentrations of growth factors at the actual site of fusion, in order to mimic the natural process of osteogenesis as closely as possible.…”
Section: Introductionmentioning
confidence: 99%